Budidaya Kentang Ramah Lingkungan Melalui Aplikasi Pupuk Organik Shisako - DARMAWATI, I.A.PUTRI; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science, 2014)
Field experiment was conducted at Antapan village, Baturiti, Tabanan Regency. The experiment aim was to study the optimals of Shisako organic fertilizer dosage for growth and yield of potato. The experiment utilized Randomized Complete Design, one factor with six rated of Shisako organic fertilizer dosage treatments. The dosage treatments were: D0 = 0 ton/ha, D1 = 2,5 ton/ha, D2 = 5 ton/ha, D3 = 7,5 ton/ha, D4 = 10 ton/ha and D5 = 12,5 ton/ha. The results showed that Shisako organic fertilizer dosage was highly significantly different to plant height, leaf number, leaf area index, tubers number per hill, tuber fresh weight per hill and fresh tubers weight per hectare than control. The optimum of Shisako fertilizer dosage treatment for microtuber Granola of potato cultivars from this research was found at 6,08 ton/ha with the maximum wet weight tubers was 5,13 ton/ha.
Keywords: Shisako fertilizers, Granola potato cultivars